The Use of Business Model Canvas for The Organizational Development at the Al Hanif Integrated Islamic High School - Istiqomah Istiqomah (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2022)
This article aims to determine how the organizational development of SMP IT Al Hanif by using a canvas business model based on the results of a SWOT analysis. This research is a case study research. Research data obtained through interviews and observations are then presented in the form of a business model canvas and analyzed with strengths, weaknesses, opportunities, and challenges. The results are used to refine the canvas business model that has been implemented so far. The results showed that the canvas business model applied at SMP IT Al Hanif was very good, especially in the elements of the value proposition, revenue stream, key resources, cost structure, and revenue relations. The MBC that has been carried out on several elements has been very good and must continue to be developed, especially in the value proposition, key activities, and cost structure. The development of SMP IT Al Hanif using MBC based on the results of SWOT analysis was carried out by (a) maintaining the existing one and running well and (b) adding other things for development. Elements that need to be improved are key partners, channels, key resources, channels. Research on the development of educational organizations using MBC needs to be carried out on other educational organizations so that organizations can develop by developing their potential.